1982
DOI: 10.1172/jci110433
|View full text |Cite
|
Sign up to set email alerts
|

Identification and measurement of molecular variants of cholecystokinin in duodenal mucosa and plasma. Diminished concentrations in patients with celiac disease.

Abstract: A B S T R A C T The amount and type of cholecystokinin (CCK) in duodenal extracts and plasma of celiac patients and normal subjects was studied by radioimmunoassay and gel filtration. In both groups there were similar patterns of molecular forms in extracts of duodenal biopsies, but concentrations in celiac disease were significantly depressed. In boiling water extracts of duodenal mucosa from both groups a factor with the properties of the COOH-terminal octapeptide of cholecystokinin predominated, but there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(63 citation statements)
references
References 20 publications
3
58
0
2
Order By: Relevance
“…Sodium paraaminohippurate (PAH) infusion and endogenous creatinine clearance were used to estimate ERPF and GFR, respectively (Calam et al, 1983 Laboratory analyses ofptasma and urine Previously described techniques (Calam et al, 1983) were used to measure electrolytes, including calcium and phosphate, PAH, creatinine, PCV and plasma renin activity (PRA; by radioimmunoassay). CCK8-like immunoreactivity concentrations (CCK8-LI) were determined by radioimmunoassay using a Cterminal specific CCK/gastrin antibody (Calam et al, 1982 …”
Section: Study Protocolsmentioning
confidence: 99%
“…Sodium paraaminohippurate (PAH) infusion and endogenous creatinine clearance were used to estimate ERPF and GFR, respectively (Calam et al, 1983 Laboratory analyses ofptasma and urine Previously described techniques (Calam et al, 1983) were used to measure electrolytes, including calcium and phosphate, PAH, creatinine, PCV and plasma renin activity (PRA; by radioimmunoassay). CCK8-like immunoreactivity concentrations (CCK8-LI) were determined by radioimmunoassay using a Cterminal specific CCK/gastrin antibody (Calam et al, 1982 …”
Section: Study Protocolsmentioning
confidence: 99%
“…Contained within peak A are three different fragments, one with COOH-terminal immunoreactivity and two having NH2-terminal immunoreactivity. The first of the NH2-terminal activity peaks (fractions [22][23][24][25][26] is probably spillover from peak B because refractionation of peak B on HPLC reveals a major NH2-terminal activity peak in this region. The second NH2-terminal activity peak may correspond to the peak 2 found in brain extracts.…”
Section: Methanol Extractmentioning
confidence: 99%
“…Generally, acid extraction has been considered optimal for extraction ofintact CCK33 (23). In previous studies the tissues to be assayed generally have been divided in half, one part extracted for the acidic COOH-terminal fragments and the other extracted with an acid extractant for the more basic intact CCK or its NH2-terminal fragments (12,16,21,24). The method described in the present report has two principal advantages over those previously described: the amount of tissue available for extraction -is effectively doubled because both acidic and basic peptides are extracted from the same tissue; and methanol is equally as effective as boiling water or alkali in extracting the COOH-terminal fragments while minimizing the extraction of the larger CCK forms that occurs with the other extractants (16,24).…”
Section: Methanol Extractmentioning
confidence: 99%
“…Phe-NH 2 ) accounts for 60% of the CCK family expressed in the human body and exhibits stronger activity than CCK33; in rats, it induces gallbladder contraction and amylase secretion in the pancreatic acini. [6][7][8][9] Binding site of CCK with its specific receptors is known to exist around the C-terminal region, which involves two methionine (Met) residues, 28 Met and 31 Met. We previously reported that the hydroxyl radical generated in vitro (Fenton's reaction) or hydrogen peroxide (H 2 O 2 ) can oxidize 28 Met and 31 Met of CCK8 to produce a CCK8 sulfoxide or sulfone [ Fig.…”
Section: Introductionmentioning
confidence: 99%